Državni topografsko-kartografski sistem - Smodiš, Martin (Geodetski vestnik, 1998)
The Surveying and Mapping Authority of the Republic of Slovenia is in charge of the national topographic-cartographic system and is setting it up according to the principle of gradual modular upgrading, particulary in free space. Acceptable solutions are sought within the framework of relatively limited funding and the required dynamics and capacities of contractors, taking into account the needs of users and developmental trends in Slovenia and abroad. The purpose of this paper is to describe the present simulation and the basic orientation of the Surveying and Mapping Authority of the Republic of Slovenia
Keywords: geodezija; kartografija; prostorske baze; prostorski podatki; Slovenija